FAKTOR - FAKTOR YANG MEMPENGARUHI TAX EVASION - Niken Sari, 15.05.52.0198; Meita Oktaviani, Rachmawati (Students' Journal of Accounting and Banking, 2019)
This study aims to empirically examine the influence of money ethics, intrinsic religiosity, extrinsic religiosity, accuracy of allocation, information technology and communication on tax evasion. The population in this study were MSME Tax Payers in Demak Regency as many as 100 MSMEs in 10 Sub-Districts namely, Dempet, Gajah, Karangayar, Wonosalam, Demak, Karang Tengah, Sayung, Karangawen, Mijen, Mranggen. The method used is the Convenience Sampling method, which is a method of selecting samples based on convenience, where this method selects samples from elements of the population whose data is easily obtained by researchers. The test equipment in this study uses the multiple linear regression test. The results of this study are money ethics, intrinsic religiosity and the accuracy of allocation, information and communication technology does not affect tax evasion. Extrinsic religiosity and information have an effect on tax evasion.